Tuning Magnetic Anisotropy Through Ligand Substitution in Five-Coordinate Co(II) Complexes - Schweinfurth, David; Krzystek, J; Atanasov, Mihail; Klein, Johannes; Hohloch, Stephan; Telser, Joshua; Demeshko, Serhiy; Meyer, Franc; Neese, Frank; Sarkar, Biprajit (Inorganic chemistry, 2017)
Understanding the origin of magnetic anisotropy and having the ability to tune it are essential needs of the rapidly developing field of molecular magnetism. Such attempts at determining the origin of magnetic anisotropy and its tuning are still relatively infrequent. One candidate for such attempts are mononuclear Co(II) complexes, some of which have recently been shown to possess slow relaxation of their magnetization. In this contribution we present four different five-coordinated Co(II) complexes, 1-4, that contain two different "click" derived tetradentate tripodal ligands and either Cl or NCS as an additional, axial ligand. The geometric structures of all four complexes are very similar. Despite this, major differences are observed in their electronic structures and hence in their magnetic properties as well. A combination of temperature dependent susceptibility measurements and high-frequency and -field EPR (HFEPR) spectroscopy was used to accurately determine the magnetic properties of these complexes, expressed through the spin Hamiltonian parameters: g-values and zero-field splitting (ZFS) parameters D and E. A combination of optical d-d absorption spectra together with ligand field theory was used to determine the B and Dq values of the complexes. Additionally, state of the art quantum chemical calculations were applied to obtain bonding parameters and to determine the origin of magnetic anisotropy in 1-4. This combined approach showed that the D values in these complexes are in the range from -9 to +9 cm . Correlations have been drawn between the bonding nature of the ligands and the magnitude and sign of D. These results will thus have consequences for generating novel Co(II) complexes with tunable magnetic anisotropy and hence contribute to the field of molecular magnetism.